Optimalisasi Produk “Jus Lia” Desa Tepisari Kabupaten Sukoharjo melalui Pelatihan Digital Marketing - Al Ayyubi, Muhammad Faiz; Kusumawardani, Anggraini Putri; Mundy, Ken Cita (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Tepisari Village, Sukoharjo Regency has local potential in the form of abundant aloe vera plants that can be used as a source of community economy. However, this potential has not been able to be maximized by the community. This research aims to examine how digital marketing training can increase the economic value of aloe vera through products in the form of "Lia Juice". The method used in this research is a qualitative method with an analytical descriptive approach. The results showed that the conversion of aloe vera into juice is expected to increase the economic value of the plant. The digital marketing training conducted also helps increase the community's understanding of sales variations so that it is expected to increase marketing results. The empowerment carried out brings the village towards self-sufficiency because it is able to optimize existing potential.